The Digital Satellite Broadcasting System in Italy: Between Mix and Hybridism - Bellavita, Andrea; Colombo, Fausto (Javnost-The Public, 2002)
This paper sets out to investigate the development of the satellite TV phenomenon as one of the first steps towards the complete digitisation of the media in Italy. Of major importance is the set of circumstances that led a small terrestrial broadcasting company, Telepiů, to become the biggest digital TV service provider in Italy and one of the most important within Europe. Before putting forward any hypothesis about the future of Sky Italia as a new player, it is necessary to analyse the most recent changes within the duopoly Telepiů and Steam. These changes took place against the background of the predominance of generalist broadcasters and was primarily driven by the opportunity to broadcast content that was not available to traditional media, in a situation characterised by economic and legislative weakness. Digital technology at present can be considered an "unpopular" medium: it doesn't have social appeal because it doesn't get onto the audience' s social agenda. This can be inferred from the low level of subscription up-take and is confirmed by evidence of widespread technological incompetence among customers. At first sight, satellite digital TV seems to be a part of a recent technological convergence trend sweeping Europe, targeting TV as a whole. But on closer inspection, it is narrowly focussed in Italy on football and sport in general. Satellite digital TV in its current phase is built on access to football rights and is prevented from becoming a genuinely new broadcasting system in Italy because it is controlled by the narrow interests of its owners and controllers, the major players in the global entertainment market.